Voltage Controlled Boost Converter-Inverter System for Photovoltaic Applications - Duranay, Zeynep Bala; Guldemir, Hanifi (My University, 2020)
Photovoltaic electric energy generation systems are attractive for the places far from the electric grid system and for small scale applications. Off-grid inverters are widely used in renewable energy applications. Most of the applications such as home appliances require constant voltage. Thus, the voltage of the inverter needs to be kept constant. In this paper, the analysis, modelling, control and simulation of a photovoltaic module fed boost converter-inverter system is studied. The PV fed boost converter provides dc link for the inverter. The cascade connection of boost converter and an inverter provides sinusoidal voltage to the ac loads. A conventional proportional+integral (PI) controller is used to obtain a constant dc link voltage even with input voltage variations. Matlab-Simulink programming environment is used for the modelling and simulations. The simulation results are presented.
Keywords: Inverter; Boost converter; voltage regulation; dc link control; off-grid inverter